Pengabdian Kepada Masyarakat Di Desa Kumpai: Self Report: Community Service in Kumpai Village: Self Report - Witri Lusdiandari; Rifqi Muhammad; Ahmad Zabidi; Manja Manja; Yusrain Yusrain; Enik Sartika (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
The purpose of this paper is to report court activities to the community in Kumpai village. The service report method uses self-report-based descriptive qualitative, primary data sources based on the log book of students of the Islamic guidance and counseling study program at the Faculty of Da'wah and Humanities IAIS Sambas on behalf of Witri Lusdiandari. The location of the service is in the village of Kumpai, Sambas District, in 2022. The community service activities include: Meetings with hamlet heads and residents at the Baitul Rahman Mosque; Gathering with community leaders at the house of the head of the border hamlet; Participate in special posyandu activities for stunting children; Teaching at Teratai PAUD TPQ activities at the Baitul Rahman Mosque; Teaching TPQ at the Al-Jihad Mosque; Implementation of the Prophet's Birthday Mini TPQ competition at the Baitul Rahman mosque; Recitation with mothers at the Al-Jihad Mosque; Tabligh Akbar at the Baitul Rahman Mosque.